Contact Lens-Associated Acanthamoeba Keratitis in Iran - AH Maghsood; M Rezaian; F Rahimi; SA Ghiasian; Sh Farnia (Tehran University of Medical Sciences, 2005)
Acanthamoeba keratitis is a vision-threatening infection caused by pathogenic species of the genus Acanthamoeba. In this study, 13 Acanthamoeba keratitis cases were diagnosed among 52 keratitis patients. To confirm the identity of Acanthamoeba at the genus level, a PCR-based method was used, and their pathogenic potential was determined using in vitro cytotoxicity assays on human corneal epithelial cells. Twelve (92.3%) of Acanthamoeba keratitis patients were contact lens wearers; among them eleven (91.7%) wore soft contact lenses. 11/13 (84.6%) isolates were axenised in liquid culture medium, of which 10 (90.9%) isolates disrupted corneal cells. Nine (69.2%) isolates showed Acanthamoeba sp. group II, and four (30.8%) showed group III morphology. To our knowledge this is the first report of determination of Acanthamoeba pathogenicity in Iran. This study confirms the importance of determination of pathogenic potential of Acanthamoeba isolates for clinical purposes.